Cardiac Magnetic Resonance Imaging in Diagnostics and Cardiovascular Risk Assessment - Patrycja S. Matusik; Katarzyna Mikrut; Amira Bryll; Tadeusz J. Popiela; Paweł T. Matusik (Diagnostics)
Cardiac magnetic resonance (CMR) allows for analysis of cardiac function and myocardial tissue characterization. Increased left ventricular mass (LVM) is an independent predictor of cardiovascular events; however, the diagnosis of left ventricular hypertrophy and its prognostic value strongly depend on the LVM indexation method. Evaluation of the quantity and distribution of late gadolinium enhancement assists in clinical decisions on diagnosis, cardiovascular assessment, and interventions, including the placement of cardiac implantable electronic devices and the choice of an optimal procedural approach. Novel CMR techniques, such as T1 and T2 mapping, may be used for the longitudinal follow-up of myocardial fibrosis and myocardial edema or inflammation in different groups of patients, including patients with systemic sclerosis, myocarditis, cardiac sarcoidosis, amyloidosis, and both ischemic and non-ischemic cardiomyopathy, among others. Moreover, CMR tagging and feature tracking techniques might improve cardiovascular risk stratification in patients with different etiologies of left ventricular dysfunction. This review summarizes the knowledge about the current role of CMR in diagnostics and cardiovascular risk assessment to enable more personalized approach in clinical decision making.